DEVELOPMENT PERSPECTIVES OF NEW GENERATION MEDICATIONS BASED ON THE REDOX SYSTEM REGULATORS - Svetlana Shahmardanova; Olga Gulevskaya; Pavel Galenko-Yaroshevsky; Pavel Kolesnichenko (Research Results in Pharmacology, 2016)
This survey paper describes the necessity of the development of new medications influencing the body redox-potential. It supports the most pressing branch of pharmacology, which coincides with logically relevant attempts to shift paradigm of pharmacology from molecular to electronic, quantum-wave. This article covers and logically assorts research results of recent years and opinions of wide range of scientists from various countries. The authors also give their own assessment of the possibility to influence body redox potential. It is reported that some biophysical achievements regarded undoubtedly put a new spin in pharmacology of the biophysical level. These research results devoted to the role of redox-potential in regulation of biological systems are considered to open up new opportunities for pharmacotherapy of pathological conditions by developing medications of the new generation – redox-potential regulators - aimed at the induction of the body protective resources. The paper further reports that elaborate study of redox-potential in providing biological systems regulation has resulted in the detailed investigation of Mexidol benefits. Special attention is paid to the general principle of action of endogenous redox regulators: metabolic, energetic and informational. The article also highlights key issues of the regulation of oxidation-reduction processes in the body and, consequently, the role of reactive oxygen species in physiology and pathology. The paper reasonably concludes with the statement on the necessity to turn pharmacologists’ attention not only to improving the existing anti-oxidant preparations, but to developing the redox system regulators, which appear to be medications of the new generation for pathogenic therapy